Social Comparison Affects Brain Responses to Fairness in Asset Division: An ERP Study with the Ultimatum Game - Wu, Yin; Zhou, Yuqin; van Dijk, Eric; Leliveld, Marijke C.; Zhou, Xiaolin (Frontiers in Human Neuroscience, 2011)
Previous studies have shown that social comparison influences individual’s fairness consideration and other-regarding behavior. However, it is not clear how social comparison affects the brain activity in evaluating fairness during asset distribution. In this study, participants, acting as recipients in the ultimatum game, were informed not only of offers to themselves but also of the average amount of offers in other allocator-recipient dyads. Behavioral results showed that the participants were more likely to reject division schemes when they were offered less than the other recipients, especially when the offers were highly unequal. Event-related brain potentials (ERPs) recorded from the participants showed that highly unequal offers elicited more negative going medial frontal negativity (MFN) than moderately unequal offers in an early time window (270-360 ms) and this effect was not significantly modulated by social comparison. In a later time window (450-650 ms), however, the late positive potentials (LPPs) were more positive for moderately unequal offers than for highly unequal offers when the other recipients were offered less than the participants, whereas this distinction disappeared when the other recipients were offered the same as or more than the participants. These findings suggest that the brain activity in evaluating fairness in asset division entails both an earlier (semi-) automatic process in which the brain responds to fairness at an abstract level and a later appraisal process in which factors related to social comparison and fairness norms come into play.